Chiral Lewis acids in organic synthesis - Mlynarski, Jacek (Wiley-VCH, 2017)
A complete overview covering the application of metal-based chiral Lewis acids from all parts of the periodic table, the Author emphasizes the most recent contributions to the field as well as prominent direction of development. The book discusses the design of chiral complexes as well as a wide spectrum of reactions promoted by various chiral Lewis acids, including water-compatible acids as well as the most important applications in the chemical and pharmaceutical industries. A must-have for catalytic and organic chemists working in the field, both in academia and industry, as well as pharmaceutical and medicinal chemists.